1989
DOI: 10.1159/000213012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise on Postural Sway in the Elderly

Abstract: Fifty female subjects, aged 72–92 (mean 82) years, were enrolled in a 12-week (36 classes) exercise program aimed at increasing postural stability. Subjects were residents of sheltered apartments, rest homes or nursing homes, well enough and mobile enough to participate in the classes. The subjects were randomized into an exercise or a control group. Their postural sway, standing at rest on a force platform, was measured with eyes open and eyes closed. The groups were well matched in all respects. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 17 publications
6
56
0
Order By: Relevance
“…The fact that the center of gravity was less disturbed over Ingersoll, Stone, & Krause, 2002). Many studies have predicted the elderly's risk of falling by analyzing COP parameters (Piirtola & Era, 2006;Pajala et al, 2008), and validated the effectiveness of balance training programs (Crilly, Willems, Trenholm, Hayes, & DelaquerriereRichardson, 1989;Judge, Lindsey, Underwood, & Winsemius, 1993). In the present study, we found significant differences in AP COP, ML COP, total COP, and COP 90 area between before and after the 8-week training (p < .05), which means that the movement trajectories of the older adults' center of gravity significantly declined.…”
Section: Kjsbsupporting
confidence: 67%
“…The fact that the center of gravity was less disturbed over Ingersoll, Stone, & Krause, 2002). Many studies have predicted the elderly's risk of falling by analyzing COP parameters (Piirtola & Era, 2006;Pajala et al, 2008), and validated the effectiveness of balance training programs (Crilly, Willems, Trenholm, Hayes, & DelaquerriereRichardson, 1989;Judge, Lindsey, Underwood, & Winsemius, 1993). In the present study, we found significant differences in AP COP, ML COP, total COP, and COP 90 area between before and after the 8-week training (p < .05), which means that the movement trajectories of the older adults' center of gravity significantly declined.…”
Section: Kjsbsupporting
confidence: 67%
“…An alternative explanation is that women with Colles' fracture are more likely to fall than those with vertebral fracture. In this regard, Crilly et al (7) reported that women with Colles' fracture had more postural instability than age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies of bone loss from the distal radius in patients with Colles' fracture scanned at sites proximal to the fracture site (3,4,(6)(7)(8)(9), where the bone is mainly cortical; at those sites bone mineral content was 5-7% below normal. The one exception was the study by Hesp et al (5) in which UDR-BMD was measured by a combined computed tomography/ single photon absorptiometry technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies of gait and balance reported some statistically significant improvements attributable to exercise (11,34,45,46,54,76,95). Another positive study is not included in Table 1 not report detailed data (77).…”
Section: Exercise Effects On Gait Balance and Physical Functionmentioning
confidence: 99%